Dolby Laboratories, Inc. - Glazer, Rashi; Bellinger, John; Schoonover, Mike; Taylor, Josie; Grace, Stacey (London : SAGE Publications Ltd, 2017)
Dolby had led the development of noise reduction technology in both the film and music industries and in 1992 decided to enter the TV broadcast market with its latest technology, Dolby Digital. By 2002, the company had succeeded in placing Dolby Digital in over 33 million TV set-top boxes worldwide through licensing agreements and had convinced most major networks to encode their programs for Dolby Digital. In 2002, the company focused on developing new products to help TV broadcasters and cable providers further enhance the sound experience for TV viewers. Their new LM100 technology would clearly benefit end users. The question was, who would pay for it?
Originally published in Glazer, R., Bellinger, J., Schoonover, M., Taylor, J., & Grace, S. (2006). Dolby Laboratories, Inc. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Dolby Laboratories Inc; Marketing; New products; Television broadcasting